Prevalence and characteristics of Livestock-Associated Methicillin-Resistant Staphylococcus aureus (LA-MRSA) isolated from chicken meat in the province of Quebec, Canada. - Jocelyn Bernier-Lachance; Julie Arsenault; Valentine Usongo; Éric Parent; Josée Labrie; Mario Jacques; François Malouin; Marie Archambault (PLoS ONE)
This study was conducted to estimate the prevalence of Livestock-Associated Methicillin-Resistant Staphylococcus aureus (LA-MRSA) in retail chicken meat and broiler chickens from the Province of Quebec, Canada, and to characterize LA-MRSA isolates. A total of 309 chicken drumsticks and thighs were randomly selected in 2013 from 43 retail stores in the Monteregie. In addition, nasal swabs and caeca samples were collected in 2013-2014 from 200 broiler chickens of 38 different flocks. LA-MRSA was not detected in broiler chickens. Fifteen LA-MRSA isolates were recovered from four (1.3%) of the 309 chicken meat samples. Multi-Locus Sequence Typing (MLST) and SCCmec typing revealed two profiles (ST398-MRSA-V and ST8-MRSA-IVa), which were distinct using pulse-field gel electrophoresis (PFGE) and microarray (antimicrobial resistance and virulence genes) analyses. In addition to beta-lactam resistance, tetracycline and spectinomycin resistance was detected in all isolates from the 3 positive samples of the ST398 profile. Southern blot hybridization revealed that the resistance genes aad(D) and lnu(A), encoding resistances to aminoglycosides and lincosamides respectively, were located on plasmid. All isolates were able to produce biofilms, but biofilm production was not correlated with hld gene expression. Our results show the presence of two separate lineages of MRSA in retail chicken meat in Quebec, one of which is likely of human origin.